DIARE ROTAVIRUS PADA ANAK DIBAWAH USIA 3 TAHUN YANG DIRAWAT DI RSU DR. SAIFUL ANWAR MALANG TAHUN 2005 (PRELIMINARY STUDY) - Santoso, Nurtjahjo Budi; Hamid, Aulia Abdul; Santoso, Sanarto (Jurnal Kedokteran Brawijaya, 2004)
ABSTRACT Rotavirus is the most common cause of acute diarrhea among children worldwide. The majority of the cases required hospitalization. Epidemiologic pattern and clinical manifestation could be helpful in establishing the proper diagnosis and management. To find out prevalence and the clinical pictures of rotavirus diarrhea among children under three years of ages with acute diarrhea admitted in the Department of Child Health Dr. Saiful Anwar General Hospital. The stools of children under three years of age with acute diarrhea between March 1st and May 1st, 2005 were assessed for rotavirus using Latex agglutination test (Slidex, Rota K2, bio Merieux). Age, sex, clinical sign and symptoms and breast-fed were recorded. The severity of acute diarrhea was estimated using WHO criteria. Statistical analysis were performed using EpiInfo 2000 program with x2 or x2 for trend. From the 40 patients with acute diarrhea were found 16 patients (40%) with rotavirus positive, both male and female were 8 patients (50%). Distribution of rotavirus positive patients in age group were 0-5 months 3/16 (18,7%), 6-11 months 6/16 (37,5%), 12-23 months 6/16 (37,5%) and 24-36 months 1/16 (6,3%). Clinical manifestations showed that most children had fever (75%), vomiting (87.5%) and dehydration (87.5%). Rotavirus infection among breast-fed patients were found less than bottle-fed patients.